Cues and economy in the acquisition of verb movement - Bentzen, Kristine (Universitetet i Tromsø, 2004)
In special issue: Tromsø Working Papers in Language Acquisition In this paper we will discuss how economy principles interact with cues in the input in bilingual first language acquisition. We will look at the acquisition of verb placement in a child acquiring English and Norwegian simultaneously. Based on data from this child, it will be argued that when faced with ambiguous cues with respect to the verb movement parameter, children do not necessarily adopt the default, less marked setting. Rather, they may opt for a setting which yields an overall consistent grammar, even when this grammar contains operations that are more costly than those used in the target language. We will suggest that economy in acquisition may involve consistency in a grammar in correlation with economy in the more traditional sense within minimalism, where moving an element in general is considered more costly than not moving it (Chomsky 1995).